Influence of the Inter Teeth Volumes on the Noise Generation in External Gear Pumps - FIEBIG, Wiesław (Archives of Acoustics, 2014)
The paper shows the new method for noise reduction in external gear pumps based on the analysis of the pressure in inter teeth volumes. The simulation model and measurement results of pressure changes in the inter teeth volume has been presented. Based on simulation results an additional volume has been obtained, which is connected to the inter teeth volume (decompression filter volume). Due this additional volume the build down processes in the pump are longer and the pressure overdue in the inter teeth volumes are smaller. This leads to the reduction of the dynamical excitation forces inside the pump and noise, especially in the higher frequency range$\,$I.